Meta-regression analysis of the effects of dietary cholesterol intake on LDL and HDL cholesterol. Issue 1 (29th December 2018) - Vincent, Melissa J; Allen, Bruce; Palacios, Orsolya M; Haber, Lynne T; Maki, Kevin C
ABSTRACT: Background: Elevated low-density lipoprotein (LDL) cholesterol is a major risk factor for cardiovascular disease. Dietary guidance recommends reducing saturated fatty acid, trans fatty acid, and cholesterol intakes to reduce circulating LDL cholesterol. Cholesterol intake may also affect high-density lipoprotein (HDL)–cholesterol concentrations, but its impact has not been fully quantified. Objectives: The aims of this study were to investigate the dose-response relation between changes in dietary cholesterol intake and changes in lipoprotein-cholesterol markers for cardiovascular disease risk and to provide a reference for clinicians on how changes in dietary cholesterol intake affect circulating cholesterol concentrations, after accounting for intakes of fatty acids. Methods: We used a Bayesian approach to meta-regression analysis, which uses Markov chain Monte Carlo techniques, to assess the relation between the change in dietary cholesterol (adjusted for dietary fatty acids) and changes in LDL and HDL cholesterol based on the use of data from randomized dietary intervention trials. Results: Fifty-five studies (2652 subjects) were included in the analysis. The nonlinear Michaelis-Menten (MM) and Hill models best described the data across the full spectrum of dietary cholesterol changes studied (0–1500 mg/d). Mean predicted changes in LDL cholesterol for an increase of 100 mg dietary cholesterol/d were 1.90, 4.46, and 4.58 mg/dL for the linear, nonlinear MM, and Hill models, respectively. Conclusions: The change in dietary cholesterol was positively associated with the change in LDL-cholesterol concentration. The linear and MM models indicate that the change in dietary cholesterol is modestly inversely related to the change in circulating HDL-cholesterol concentrations in men but is positively related in women. The clinical implications of HDL-cholesterol changes associated with dietary cholesterol remain uncertain.